Design and Development of a Web-Based Construction Service Information System for CV. Open The Sky - Utomo, Reynaldo Rahadian; Sharyanto, Sharyanto; Whendasmoro, Raditya Galih (Journal of Mathematics and Technology (MATECH), 2025)
CV. Open The Sky is a construction service company facing challenges in project management and client communication due to manual systems. This leads to information delays, data duplication, and a lack of efficiency and transparency. This research aims to design and develop a web-based construction service information system to improve project management efficiency, accelerate administrative processes, and enhance communication. The methods used include observation, interviews, literature review, and a system design approach using UML. Development was carried out using the Laravel framework with a MySQL database, while system testing was conducted using the Black Box method. The results show the designed system can manage project data structurally, support real-time monitoring, and provide transparent information access to clients. With this system, CV. Open The Sky can improve operational performance, accelerate decision-making, and increase customer satisfaction.